Assessment of turbulence model performance adopted near wall treatment for a sharp 90° 3-D turning diffuser - Nordin, N. (Springer Verlag, 2017)
The primary aim of this paper is to assess the performance of k-ε turbulence models by means of adopting various near wall treatments to simulate the flow within a sharp 90° 3-D turning diffuser. The Computational Fluid Dynamics (CFD) results were validated quantitatively and qualitatively with the experimental results (using Particle Image Velocimetry (PIV)). The standard k-ε adopted curvature correction and enhanced wall treatment of y+ ≈ 1.2–1.7 appears as the best validated model, producing minimal deviation with comparable flow structures to the experimental cases. © Springer Nature Singapore Pte Ltd. 2017.